Fully synthetic phosphorylated Tau181, Tau217, and Tau231 calibrators for Alzheimer’s disease diagnosis - Li, Xinyu; Zeng, Huimei; Durairaj, Pradeepraj; Wen, Weihuan; Li, Tianpeng; Zhao, Yanru; Liu, Yang; Liu, Xue; Zhan, Lingpeng; Rao, Lang; Yuan, Wen; Guo, Tengfei; et al. (Frontiers in Aging Neuroscience, 2024)
Background: The calibrator in immunoassay plays an essential role in diagnosing Alzheimer's disease (AD). Presently, the most well-studied biomarkers for AD diagnosis are three phosphorylated Tau (p-Tau): p-Tau231, p-Tau217, and p-Tau181. Glycogen synthase-3beta (GSK3β)-phosphorated Tau-441 is the most commonly used calibrator for p-Tau immunoassays. However, the batch-to-batch inconsistency of the commonly used GSK3β-phosphorylated Tau-441 limits its clinical application.Methods: We have successfully generated and characterized 61 Tau monoclonal antibodies (mAbs) with distinct epitopes by using the hybridoma technique and employed them as capture or detection antibodies for p-Tau immunoassays. Through chemical synthesis, we synthesized calibrators, which are three peptides comprising two epitopes, as well as capture and detection antibody epitopes, for application in immunoassays that detect p-Tau231, p-Tau217, and p-Tau181. The novel calibrators were applied to Enzyme-linked immunosorbent assay (ELISA) and Single-molecule array (Simoa) platforms to validate their applicability and establish a range of p-Tau immunoassays.